Estimation of irrigated crops areas: generation of water demand scenarios - Montesinos S.; Fernández L. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
The study of the evolution of agricultural demand is one of the most significant aspects for water management, not only due to the specific weight that it represents inside the global river basin demand, but also to the difficulty to estimate it. The irrigated area map is elaborated from digital processing of available satellite images, and is based in the analysis, interpretation and classification of vegetation index maps, where numerical information is collected and is linked with the photosynthetic activity rate, vegetation cover vigour and vegetation vigour within each crop.